BIOLOGICAL ACTIVITY OF VALACYCLOVIR DERIVATIVES OF [(2-AMINO-9-((2-HYDROXY ETHOXY)ETHYL)-1H-PURINE-6(9H)-ONE) ]. - CHAITRAMALLU M, PARVATHI G R, B S SUJATHA, SINDHU G M (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Valacyclovir is a synthetic purine nucleoside analogue that has been approved by FDA as an antiviral drug. One of the most commonly used valacyclovir which works at lower concentration than acyclovir is a very old drug that was used during Severe Acute Respiratory Syndrome Coronavirus 2 infection worldwide. DPPH radical scavenging assay, Hydroxyl scavenging, DNA binding and protecting assay, antimicrobial activity and ATPase activity of 2-amino-9-((2-hydroxy ethoxy) methyl)-1H-purin-6(9H)-one derivatives were assessed. Among the selected guanine derivatives SA-A to J, SA-D analogue possessed comparatively highest DPPH radical scavenging potential, hydroxyl radical scavenging activity. The guanine derivatives B, C, F, H comparatively showed excellent DNA protecting activity. SA-A to SA-J responded differentially to gram positive and gram negative bacterial cultures. H+/K+ ATPase inhibition activity of tested guanine analogues revealed that SA-E has higher inhibitory potency. In the present investigation, the biological screening of 2-amino-9-((2-hydroxy ethoxy) methyl)-1H-purin-6(9H)-one derivatives responded differentially and to summarize SA-D analogue is a strong antioxidant and SA-E is comparatively potent Gastric H+ /K+ ATPase inhibitor.